The latent factor structure and assessment of childbirth-related PTSD: psychometric characteristics of the City Birth Trauma Scale—Persian version (City-BiTS-P) - Vatanparast, Amin; Kamrani, Ali; Shakiba, Shima; Amouchie, Ramin; Akbari, Elnaz; Ayers, Susan (Frontiers in Psychiatry, 2023)
Objective: There is no validated Persian questionnaire to measure childbirth-related PTSD (CB-PTSD) symptoms. In order to cover this gap, the present study aimed to provide a Persian version of the City Birth Trauma Scale (CityBiTS-Pr) and to determine its psychometric properties. Method: This is a cross-sectional study. Sampling was done by using a convenient sampling method. In total, 300 Persian speaking women took part in this study and completed the City Birth Trauma Scale (CityBiTS-Pr), the Posttraumatic Stress Disorder Checklist for DSM-5 (PCL-5), the Edinburgh Postnatal Depression Scale (EPDS), and the Anxiety subscale of the Depression, Anxiety and Stress Scale (DASS-21). In addition, socio-demographic information was completed. Confirmatory factor analysis of two and four factor models, and a bi-factor model with a general factor and two specific factors was tested. Fit indices were calculated for all three models. Reliability, convergent, divergent, and discriminant validity also were examined. R v4.2.1 and SPSS v23 were used for data analysis. Results: The four-factor model comprised of intrusion, avoidance, negative cognitions and mood, and hyper-arousal showed a poor fit. The two-factor model composed of “birth-related symptoms” and “general symptoms” provided the best results based on all fit indices. The bi-factor result was relatively good, but the loadings indicated that the general symptoms factor is not well defined. Conclusion: The Persian version of the City Birth Trauma Scale (CityBiTS-Pr) is a valid and reliable questionnaire for evaluating postpartum PTSD.